2024
DOI: 10.1111/echo.15753
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial strain of the left ventricle by speckle tracking echocardiography: From physics to clinical practice

Elisa Gherbesi,
Silvia Gianstefani,
Francesco Angeli
et al.

Abstract: Speckle tracking echocardiography (STE) is a reliable imaging technique of recognized clinical value in several settings. This method uses the motion of ultrasound backscatter speckles within echocardiographic images to derive myocardial velocities and deformation parameters, providing crucial insights on several cardiac pathological and physiological processes. Its feasibility, reproducibility, and accuracy have been widely demonstrated, being myocardial strain of the various chambers inserted in diagnostic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 259 publications
(471 reference statements)
0
5
0
Order By: Relevance
“…In conclusion, Frimodt-Møller et al 3 observed for the first time a correlation at rest between CACS and multilayer GLS without significant coronary stenosis. Since all previous studies were able to detect GLS impairment only in patients with obstructive coronary disease, 13 these results have to be confirm by a multicenter trial. Further studies are needed to better understand the potential role of multilayer GLS assessment to detect subclinical atherosclerosis.…”
Section: Coronary Artery Calcium Score Global Longitudinal Strainmentioning
confidence: 87%
“…In conclusion, Frimodt-Møller et al 3 observed for the first time a correlation at rest between CACS and multilayer GLS without significant coronary stenosis. Since all previous studies were able to detect GLS impairment only in patients with obstructive coronary disease, 13 these results have to be confirm by a multicenter trial. Further studies are needed to better understand the potential role of multilayer GLS assessment to detect subclinical atherosclerosis.…”
Section: Coronary Artery Calcium Score Global Longitudinal Strainmentioning
confidence: 87%
“…New indices, such as global longitudinal strain and mechanical dispersion, were shown to increase the accuracy of obstructive CAD detection [38,39]. Moreover, the assessment of myocardial strain has a well-validated prognostic value [40].…”
Section: Discussionmentioning
confidence: 99%
“…Reduced work efficiency is observed in cardiomyopathies, accompanied by declines in GLS and LVEF. 2 MW assessment is based on the acquisition of transthoracic views for GLS analysis followed by non-invasive systolic BP measurement. This BP measurement, obtained using a sphygmomanometer, is crucial for estimating peak systolic pressure within the left ventricle and is input into the echocardiography system for subsequent MW analysis.…”
Section: Atrial Fibrillation Myocardial Work Strain Echocardiographymentioning
confidence: 99%